Analysis of Potential Natural Disaster Risks in Buleleng Regency - PUTRA, I Wayan Krisna Eka; DHARMA, I Gusti Bagus Sila; ASTARINI, Ida Ayu; KARANG, I Wayan Gede Astawa (PT Keberlanjutan Strategis Indonesia, 2023)
Buleleng is one of the regency in the Province of Bali which has various potential disaster risks, mainly dominated by natural disaster. This condition is influenced by the topography of the Buleleng Regency area which has the characteristics of Nyegara Gunung, namely to the north is a coastal area while to the south is a hill’s area. Based on these conditions, it is necessary to have a risk analysis of natural disasters that have the potential to occur, so that alternative disaster management can be made. This study aims to determine the potential for disaster risk in Buleleng Regency and how the priorities for handling from the level of risk and intensity of the threat. The method used in this study is an analysis of potential natural disaster risks obtained from a combination of hazard, vulnerability and capacity data. Threat data was obtained from data released by BNPB from the inarisk.bnpb.go.id, while vulnerability and capacity data were obtained from interviews and secondary data from related agencies. The entire data obtained was then conducted an FGD with BPBD Buleleng Regency which was then analyzed descriptive qualitative. Based on the research results, it was found that the potential for disasters in Buleleng Regency were categorized into 2, namely: disasters that have a high risk impact are Earthquakes and Tsunamis, while disasters with high incident intensity are floods, extreme weather, extreme waves and abrasion, drought, landslides, flash floods and fires.